Tailored implementation of the FICUS multicomponent family support intervention in adult intensive care units: findings from a mixed methods contextual analysis - Lotte Verweij; Saskia Oesch; Rahel Naef (BMC, 2023)
Abstract Background The Family in Intensive Care UnitS (FICUS) trial investigates the clinical effectiveness of a multicomponent, nurse-led interprofessional family support intervention (FSI) and explores its implementation in intensive care units (ICUs). The local context of each ICU strongly influences intervention performance in practice. To promote FSI uptake and to reduce variation in intervention delivery, we aimed to develop tailored implementation strategies. Methods A mixed method contextual analysis guided by the Consolidated Framework for Implementation Research (CFIR) was performed from March to June 2022 on eight ICUs assigned to the intervention group. ICU key clinical partners were asked to complete a questionnaire on CFIR inner setting measures (i.e., organizational culture, resources, learning climate and leadership engagement) and the Organizational Readiness for Implementing Change (ORIC) scale prior to group interviews, which were held to discuss barriers and facilitators to FSI implementation. Descriptive analysis and pragmatic rapid thematic analysis were used. Then, tailored implementation strategies were developed for each ICU. Results In total, 33 key clinical partners returned the questionnaire and 40 attended eight group interviews. Results showed a supportive environment, with CFIR inner setting and ORIC measures each rated above 3 (scale: 1 low-5 high value), with leadership engagement scoring highest (median 4.00, IQR 0.38). Interview data showed that the ICU teams were highly motivated and committed to implementing the FSI. They reported limited resources, new interprofessional information exchange, and role adoption of nurses as challenging. Conclusion We found that important pre-conditions for FSI implementation, such as leadership support, a supportive team culture, and a good learning climate were present. Some aspects, such as available resources, interprofessional collaboration and family nurses' role adoption were of concern and needed attention. An initial set of implementation strategies were relevant to all ICUs, but some additions and adaptation to local needs were required. Multi-component interventions are challenging to implement within complex systems, such as ICUs. This pragmatic, theory-guided, mixed methods contextual analysis demonstrated high readiness and commitment to FSI implementation in the context of a clinical trial and enabled the specification of a tailored, multifaceted implementation strategy.